Assessment of prescribing information for generic drugs manufactured in the Middle East and marketed in Saudi Arabia - Gebran, Nicole (Ann Saudi Med, 2006)
BACKGROUND: Little research has assessed the quality of manufacturer-provided prescribing information or documented differences in key aspects of drug information among different marketed generic products of the same drug, particularly in the Middle East and Arabian Gulf. We assessed the quality of written prescribing information for selected generic drugs marketed in Saudi Arabia and manufactured in various countries of the Middle East. METHODS: We assessed the correctness and completeness of information pertaining to indications, dosage, cautions/contraindications, side effects and drug interactions in 37 package inserts for generic products registered in Saudi Arabia and manufactured in the Middle East, including atenolol (6 inserts), fluoxetine (4 inserts), ciprofloxacin (11 inserts), metformin (7 inserts), and omeprazole (9 inserts). We also described deficiencies in the quality and quantity of manufacturer-provided information that could be misleading to patients and prescribers. RESULTS: We found substantial disagreement in information between generic package inserts versus the British National Formulary and the package insert of the brand product marketed in Saudi Arabia. A cumulative average of 63±16% of drug information indicators were in agreement with these standard references. Section headings with the least conformity with study references were those related to dosage (57± 28%) and side effects (54±30%). CONCLUSION: Our results indicate that national authorities should implement appropriate measures aimed at removing misleading and incorrect information in generic package inserts and incorporating crucial prescribing information that is missing. National authorities in the Middle East and Arabian Gulf should strengthen collaboration and information interchange among each other and with international agencies to maintain common quality standards for delivering information through package inserts.